ANALISIS NILAI SAHAM DENGAN PENDEKATAN ABSOLUTE VALUATION DAN RELATIVE VALUATION PADA PERUSAHAAN PENAMBANGAN - Meiliana Jaunanda (FEB Universitas Sam Ratulangi Manado, 2022)
Investment in Indonesia is getting more advanced from year to year. This can be seen from the IHSG has increased every year accompanied by improving economic growth in various sectors. One of the sectors that an important role in the development of the country is the mining sector. The mining sector has a high capitalization value and dominant in Indonesia and abroad. This is enough to pay attention to investors to invest their capital, but before buying and selling a stock, investors conduct an analysis first whether the shares invested are overvalued, fairvalued and undervalued. This study uses relative valuation techniques to value stocks using price book value (PBV) and price earning ratio (PER) proxies and determines whether the stock is overvalued, fairvalued and undervalued. Sampling was carried out at mining companies which consecutively distributed dividends during the 2015-2019 period. The result of this research is that ADRO, both PER and PBV in 2019, was undervalued. KKGI both PER and PBV in 2019 has been overvalued. ITMG, MYOH and PTBA under PER are undervalued and PBV overvalued.Arista, Desy. 2012.